Dampak Sosial Ekonomi Pembangunan STKIP PGRI Sumatera Barat - Eka Putri Hardiyanti (Diakronika, 2019)
ABSTRACT Construction is a process of change that is based on planned and deliberated, and demanded eiter the goverment or the society in improving the lives of more prosperous. Indonesia national construction is a construction paradigm that is built on the practice of pancasila that Indonesia fully human construction and the counstruction of Indonesia society. The construction carried out by the Indonesia goverment is essentially to improve thair living standard society. The construction impacts include the social dimension as the waning of cultural values, social norms causing forms of deviant behavior and dependence of society on the other side as a result of the intervention system construction has an impact on socioe economic conditions. So is the case with the construction of the college located in, Kampung Olo is STKIP PGRI Sumatera Barat that occurred in their socio economic society. The researchar aims to know and desribe the impacts of constructins STKIP PGRI Sumatera Barat toward economic social society Kampung Olo, Nanggalo district Padang city.In this research using Structural Functional Theory form Robert. K. Merton. Beside, the research that used is qualitative research with Descriptive type. As for the information that is taken by using purposive sampling. The number of participants is 21 participants consisting of 15 participants who trade, 3 participants from staff officer Kelurahan and Leader of RW 01 and RW 02. The type of data used primary and secondary data. Method of data colletion is done by 3 ways: 1) observations (non participant), 2) interview, 3) document analysis. To achieve the validity of the reseacrh, the researcher using triagulasi technique. The unit of analysis used is group with data analysis Milles and Huberman consist from steps are reduction, data presentation, and conclucion.Based on the result of the research found the impacts of construction STKIP PGRI Sumatera Barat in Kampung Olo, Nanggalo disrtrict Padang city. 1) Social impact which consist : a. Increasing social network the traders ang migrant society, b. Increasing social norm or more increase the regulations around Kampung Olo especially college area, c. An increase in social problems, d. Demography, the populations density of the society in Kampung Olo. 2) Economic impact: a. Change in the society’s livelihood, b. Increasing society asset after the constructions of the college, c. Increasing society’s income. Keywords: Impact of construction, Socio, Economic